Penerapan Augmented Reality Dalam Replikasi Tata Letak Studio Foto - Sandi Wahyu Maulana; Rohman Dijaya; Cindy Taurusta; Ika Ratna Indra Astutik (STMIK Budi Darma, 2023)
The role of information technology is very influential in a person's life, thanks to technology it is possible to produce various conveniences so that people get what they want. Information technology is used in different fields, one of which is the field of information transmission. In the delivery of information, it is necessary to have a visual device so that the delivery is easily understood by the community. The delivery of information is an important support for all human activities.The delivery of information, one of which is in the field of architecture through information technology, which includes hardware and software to describe various infrastructures such as buildings.However, in terms of photo studios, many photo studios only think about the design of the studio to make it look attractive without thinking about whether or not the space for taking photos taken by photographers is sufficient.So that photographers sometimes have difficulty taking pictures because the studio space is too narrow due to designs that almost fill the space or studio designs that are not suitable in the size of the room.By using this application, it is hoped that a person can determine the design that suits the studio space. The system will be built based on Android, in the application will be made with a markerless method (without marker) which means that the 3d object will come out if it is triggered with a flat field. The camera will identify a flat field and will display a studio design object that the user has chosen before. In this application there is also an import feature that aims to input new object data from the internal storage of the user's device. Produce a digital product catalog application based on Augmented reality named DeStudio, and can also help photographers to design studio designs / themes that are clear and specific by utilizing Augmented reality technology. In the testing process alpha testing was successfully applied and got 84% smooth results. In beta testing, the average results are very satisfying from some responding, meaning that the application can be used and applied without any obstacles. In the new additional features, the results are very good because the user does not bother to rebuild. Each user can add 3D objects.